Verbivocovisual : On 'Materializzazione del Linguaggio', a 1978 Venice Biennale exhibition of language-based artwork made by women. - Bennett, Alex; Gaynor, Oscar; Carson, Anne; Grandal Montero, Gustavo (London : Antenne Books, 2019)
Alloatti, Annalisa ; Bentivoglio, Mirella ; Binga, Tomaso ; Calparsoro, Blanca ; Claire, Paula ; Etlinger, Amelia ; Garnier, Ilse ; Goncharova, Natalia ; Hachette, Micheline ; Hatherly, Ana ; Ladik, Katalin ; Lanza, Sveva ; La Rocca, Ketty ; Mejía, Silvia ; Pacheco e Chaves, Anésia ; Pike, Jennifer ; Radin, Betty ; Rozanova, Olga ; Sandri, Giovanna ; Schendel, Mira ; Schödl, Greta ; Solt, Mary Ellen
Several years ago, researching the artistic movement of Concrete Poetry, we found a thin slip of a catalogue in the drawers on a private archive. In a period and a scene so dominated by men, this publication was a refreshing anomaly: 'materializzazione del linguaggio'. The exhibition, curated by Italian artist Mirella Bentivoglio, featured over eighty women artists working in a huge range of media, but united in their interrogation of text, voice and language. In No.2, we bring much of this work back to the fore where many artists have slipped into the footnotes of an exciting period in art history. But much beyond our focus on this iconic exhibition, the issue features new essays and art projects by some of the best artists working with text, voice and poetry today. (provided by publisher)
boek